Five Year Results of Off the Shelf Fenestrated Endografts for Elective and Emergency Repair of Juxtarenal Abdominal Aortic Aneurysm. (April 2021) - Sveinsson, Magnus; Sonesson, Björn; Dias, Nuno; Björses, Katarina; Kristmundsson, Thorarinn; Resch, Timothy
Abstract : Objective: Fenestrated endovascular aneurysm repair (FEVAR) is a well established treatment for complex abdominal aortic aneurysms (AAAs). FEVAR with custom made devices (CMDs) has limitations in both the emergency and elective settings due to time consuming manufacture. "Off the shelf" (OTS) fenestrated stent grafts are a potential solution. The primary goal was to evaluate the five year outcome of the COOK Zenith p-Branch OTS device at a single centre. Methods: Patients with juxtarenal AAA meeting the inclusion criteria for the COOK Zenith p-Branch device were enrolled in a prospective, non-randomised, non-comparative trial from July 2012 to September 2015. Demographic, anatomical, procedure related, and five year follow up data were collected, analysed, and adjudicated by a core laboratory. The primary aims were to assess intervention free survival and overall survival at five years. Results: Twenty-three patients were treated and 21 completed follow up. Mean time to p-Branch implantation after patient presentation was 28 hours (range 0–122 hours) in emergency cases and 67 days (range 20–112 days) in elective cases. Median procedure time was 283 minutes (range 161–475 minutes) and technical success was 91%. Mean follow up was 45 months (standard deviation ± 24.4 months). The most common adverse events were renal injuries. Primary target vessel patency was 96.4% and 94.0% after one and five years respectively. Mean time to first re-intervention was 469 days (range 0–1 567 days). Survival during the follow up period was 76%, with no aneurysm related deaths. Conclusion: FEVAR with the COOK Zenith p-Branch device is safe and effective for juxtarenal AAA in a selected patient population, in both elective and emergency settings. Long term outcomes are acceptable although inferior to CMDs. Mid and long term outcomes emphasise the p-Branch as a possible endovascular treatment for juxtarenal aortic pathology where CMD is not an option. Further innovation to address target vessel complications is needed, as these seem more prevalent than after repair with CMDs.